Archetypes in Stone Sculptures of Nepal - Sharma, Kamal (Journal of Fine Arts Campus, 2023)
In many stone sculptures of Nepal, some icons, images, and symbols are recurrent. The sculptures have symbols that suggest ideas and concepts beyond the presented images. The icons and symbols lead toward the roots of our culture, tradition, and myths. The archetypes suggest the wider ideals of meditation, wisdom, and enlightenment. The symbols and archetypes in the sculptures include the figures of gods and goddesses, lotus, Shivalinga, Trishul, and so on. These magical symbols suggest spiritual values. They create viewers aware of the unity of the self and the external world. The mythical contents seem to be mystical. In addition to the aesthetic pleasure, the visuals make us aware of our tradition, culture, myth and ancient civilization. The sense of the artworks enhances human values. The tangible compositions suggest intangible spiritual dimensions of the community. The artworks integrate primordial images and icons from cultures, myths, and rituals. The archetypes are revealed in a spontaneous manner. Nepali artists share these primordial images from their collective unconscious, the common heritage of mankind, and the storehouse of archetypes. The research paper derives the thesis statement from the interpretation of stone sculptures, and there are the possibilities of multiple interpretations works. Thus, this study is qualitative.